The South Sea Bubble and the Erasure of Slavery and Impressment. Issue 7 (3rd October 2021) - Paul, Helen
ABSTRACT: When the South Sea Bubble burst in 1720, there was an outpouring of critical commentary. This took a variety of forms but centred around common themes of fraud and ruin. Three hundred years later, there is a renewed focus on the horrors of the slave trade. In addition, slaving companies needed the help of the Royal Navy and the navy used impressment. Forced labour was an essential part of the Bubble story but is often erased from it or merely mentioned in passing. Complaints by wealthy people about their losses have drowned out the voices of the enslaved.